Islamic Law Study: Hoarding (Ikhtikar) of Natural Resources (SDA) - Azhari, Dhea Maura (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2021)
Hoarding of goods is the purchase of an item in large quantities and will resell it if the item is scarce and will increase the selling price. Hoarding of goods is an activity that is prohibited (haram) in Islamic provision based on Islamic religious books. Natural Resources should be used properly and not overused. The act of hoarding goods has a very bad impact on fellow living beings. With a limited supply of Natural Resources, we must protect and preserve it, not just enjoy it as we wish.